The Effect of Spinal Cord Stimulation Frequency on the Neural Response and Perceived Sensation in Patients With Chronic Pain - Gmel, Gerrit Eduard; Santos Escapa, Rosana; Parker, John L.; Mugan, Dave; Al-Kaisy, Adnan; Palmisani, Stefano (Frontiers in Neuroscience, 2021)
Background The effect of spinal cord stimulation (SCS) amplitude on the activation of dorsal column fibres has been widely studied through the recording of Evoked Compound Action Potentials (ECAPs), the sum of all action potentials elicited by an electrical stimulus applied to the fibres. ECAP amplitude grows linearly with stimulus current after a threshold, and a larger ECAP results in a stronger stimulus sensation for patients. This study investigates the effect of stimulus frequency on both the ECAP amplitude as well as the perceived stimulus sensation in patients undergoing SCS therapy for chronic back and/or leg pain. Methods Patients suffering with chronic neuropathic lower-back and/or lower-limb pain undergoing an epidural SCS trial were recruited. Patients were implanted according to standard practice, having two 8-contact leads (8mm inter-electrode spacing) which overlapped 2 to 4 contacts around the T9/T10 interspace. Both leads together thus spanning about 3 vertebral levels. Neurophysiological recordings were taken during the patient’s trial phase at two routine follow-ups using a custom external stimulator capable of recording ECAPs in real-time from all non-stimulating contacts. Stimulation was performed at various vertebral levels, varying the frequency (ranging from 2Hz to 455Hz) while all other stimulating variables were kept constant. During the experiments subjects were asked to rate the stimulation-induced sensation (paraesthesia) on a scale from 0 to 10. Results Frequency response curves showed an inverse relationship between stimulation sensation strength and ECAP amplitude, with higher frequencies generating smaller ECAPs but stronger stimulation-induced paraesthesia (at constant stimulation amplitude). Both relationships followed logarithmic trends against stimulus frequency meaning that the effects on ECAP amplitude and sensation are larger for smaller frequencies. Conclusions This work supports the hypothesis that SCS-induced paraesthesia is conveyed through both frequency coding and population coding, fitting known psychophysics of tactile sensory information processing. The inverse relationship between ECAP amplitude and sensation for increasing frequencies at fixed stimulus amplitude questions common assumptions of monotonic relationships between ECAP amplitude and sensation strength.